Improved CMA-FSE blind equalization algorithm for wireless ultraviolet communication - Taifei ZHAO; Longfei LIU; Jing WANG; Liyang YANG (Tongxin xuebao)
There are serious intersymbol interference (ISI) and signal attenuation in wireless ultraviolet communication system.Aiming at this problem,an improved constant modulus fractionally spaced equalizer (CMA-FSE) based on signal-to-noise (SNR) estimation was proposed.The algorithm combined the fractionally spaced equalizer (FSE) and constant modulus algorithm (CMA) for blind equalization of wireless ultraviolet channels.The input SNR was measured by the mean square value of the received signal,and it was used to determine the best iterative step to ensure the convergence of the equalization algorithm.Simulation results show that the improved CMA-FSE algorithm can converge rapidly under various SNR,and it can effectively suppress ISI and improve the BER performance of the system.Compared with the existing algorithms,the improved algorithm is more useful in channel tracking and noise suppression.